2020
DOI: 10.1002/humu.23995
|View full text |Cite
|
Sign up to set email alerts
|

Update of variants identified in the pancreatic β‐cell K ATP channel genes KCNJ11 and ABCC8 in individuals with congenital hyperinsulinism and diabetes

Abstract: The most common genetic cause of neonatal diabetes and hyperinsulinism is pathogenic variants in ABCC8 and KCNJ11. These genes encode the subunits of the β-cell ATP-sensitive potassium channel, a key component of the glucose-stimulated insulin secretion pathway. Mutations in the two genes cause dysregulated insulin secretion; inactivating mutations cause an oversecretion of insulin, leading to congenital hyperinsulinism, whereas activating mutations cause the opposing phenotype, diabetes. This review focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 107 publications
4
118
0
1
Order By: Relevance
“…Opening and closing of the potassium channel regulates glucose-stimulated insulin secretion by coupling blood glucose levels and intracellular ATP concentration to the beta cell membrane’s electrical activity. Heterozygous mutations affecting the ABCC8 gene disrupt the potassium channel’s normal function leading to impaired insulin secretion [ 47 , 61 , 62 , 102 ]. ABCC8-MODY may be characterized by congenital hypoglycemic hyperinsulinism, a transient or permanent form of neonatal diabetes mellitus, or adulthood-onset diabetes mellitus [ 61 , 62 , 102 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opening and closing of the potassium channel regulates glucose-stimulated insulin secretion by coupling blood glucose levels and intracellular ATP concentration to the beta cell membrane’s electrical activity. Heterozygous mutations affecting the ABCC8 gene disrupt the potassium channel’s normal function leading to impaired insulin secretion [ 47 , 61 , 62 , 102 ]. ABCC8-MODY may be characterized by congenital hypoglycemic hyperinsulinism, a transient or permanent form of neonatal diabetes mellitus, or adulthood-onset diabetes mellitus [ 61 , 62 , 102 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potassium channel inwardly rectifying subfamily J member 11 (KCNJ11) gene is highly expressed in the pancreas where it encodes the pore-forming Kir6.2 subunit of the ATP-sensitive potassium channel. Similar to ABCC8-MODY, heterozygous mutations in the KCNJ11 cause defective glucose-stimulated insulin secretion by disrupting the activity of the potassium channel [ 47 , 63 , 64 , 102 ]. KCNJ11-MODY may be characterized by congenital hypoglycemic hyperinsulinism, a transient or permanent form of neonatal diabetes mellitus, or late-onset diabetes mellitus [ 63 , 64 , 102 ].…”
Section: Introductionmentioning
confidence: 99%
“…E179K/A) and CHI (e.g. K67N) [16][17][18] . A previous study has shown that the K67N mutation does not alter channel surface expression but has reduced channel activation when cell metabolism was inhibited 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The repression of Kir6.2/SUR1 channels stimulates the release of insulin [60], and it has been reported that mutations and deficiencies of ABCC8 and KCNJ11 induce hyperinsulinism [61][62][63][64][65]. In various studies and clinical reports, the hypersecretion of insulin has been linked to the development of several types of cancer, including breast, colon, liver, and kidney cancers [66,67], and the survival rates through GEPIA in our research also confirmed that higher the expression levels of the two genes, the better is the survival rate ( Figure S4A).…”
Section: Discussionmentioning
confidence: 99%